2022
DOI: 10.14295/cs.v13.3703
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural ambience and salt stress in production of yellow passion fruit seedlings

Abstract: The objective was to evaluate the initial growth and gas exchange of yellow passion fruit seedlings irrigated with saline water under different environments. The experiment was conducted of the University of International Integration of Afro-Brazilian Lusophony, Redenção-CE. The experimental design used was entirely randomized, in factor arrangement 4 x 2, referring to four environments with different shade screens (black screen; whitescreen; red screen; all with 50% shading; and full sun) and the values of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Água vol. 17 n. 6, e2868 -Taubaté 2022 Similar to the results obtained in the present study, Nojosa Lessa et al (2022) analyzed the production of yellow passion fruit seedlings under saline stress and agricultural environment, and found that A/E was superior when irrigated with low salinity water in certain types of environments.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Água vol. 17 n. 6, e2868 -Taubaté 2022 Similar to the results obtained in the present study, Nojosa Lessa et al (2022) analyzed the production of yellow passion fruit seedlings under saline stress and agricultural environment, and found that A/E was superior when irrigated with low salinity water in certain types of environments.…”
Section: Resultssupporting
confidence: 83%
“…Nojosa Lessa et al (2022), state that plants exposed to sunlight under salt stress show higher rates of uptake and translocation of potentially toxic ions when compared to shaded plants. In a study evaluating the responses of sweet cherry to salt stress under different shading, Aras et al (2021), found that the stomatal conductance of the plants reduced when grown under salt stress in a non-shaded environment.…”
Section: Resultsmentioning
confidence: 99%
“…Living with this problem in semi-arid regions highlights the need to employ management strategies that reduce the impact of salinity on plants and the environment [10]. In this regard, phosphate fertilization has been tested to reduce the effects of salt stress.…”
Section: Introductionmentioning
confidence: 99%